Transition of Digital Culture for Indonesian Women in Print Magazine to Digital Magazine (Global Journal of Human-Social Science, 2014)
Magazine is an information source that is part of media industry. Moreover, magazine is also acts as an entertainment source for its readers. One of the impacts of the technological development is the transition from printed magazine to digital magazine. The development of technology creates a revolution in publishing industry, for instance this phenomenon changes the consumption habit of printed publication, which is currently in its fully mature state today. This transition give impacts to its readers. One of the examples are the digital culture from the visual point of view. In this work, we focus our observation of such a culture transition from the visual point a view on a magazine. A study case that is used in this work is from Indonesia life style magazine. This magazine is considered as one of the women magazines that have the longest history in Indonesia. A qualitative method and semi quantitative method that describes the digital culture transition from the digital culture view that occurs on both printed and digital version magazine is used in this work. Such a technological transition influences the value of the magazine with respect to its readers -Indonesian women. Media is battlefield of culture. Most of the content of the contemporary culture war is related to the image cultivated by the mass media. This struggle goes beyond morality and values, sometimes focus on the involvement of our popular media representations and the evidence of lessons learned about community media.
Keywords: transition; magazine; printed; digital; indonesian women; digital culture